2021
DOI: 10.3389/fcvm.2020.585779
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Hypertriglyceridemia and Premature Atherosclerosis in a Patient With Apolipoprotein E Gene ε2ε1 Genotype

Abstract: We present a case of a 40-year-old male with premature atherosclerosis, with evidence of both eruptive and tendinous xanthomas, which could imply an increase in both low-density lipoprotein (LDL) and triglyceride (TG) levels. However, his LDL was 2.08 mmol/l, TG -11.8 mmol/l on rosuvastatin 20 mg. Genetic evaluation was performed using a custom panel consisting of 25 genes and 280 variants responsible for lipid metabolism. A rare ε2ε1 genotype of apolipoprotein E was detected. The combination of clinical manif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
3
0
2
Order By: Relevance
“…2,5 ApoE gene polymorphisms affect lipoprotein clearing and lipid profile, and also the development of CAD. 6,7 Lipid metabolism is influenced by ApoE genotypes. A previous study found that ε4 carriers can increase CAD risk by approximately 42%.…”
Section: Introductionmentioning
confidence: 99%
“…2,5 ApoE gene polymorphisms affect lipoprotein clearing and lipid profile, and also the development of CAD. 6,7 Lipid metabolism is influenced by ApoE genotypes. A previous study found that ε4 carriers can increase CAD risk by approximately 42%.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also suggested that genetic variations in APOE may contribute to the development of RA [61]. • MMP-3: Matrix metalloproteinase-3 (MMP-3) is an enzyme in tissue remodeling and repair [62].…”
Section: Shared Genes For Rheumatoid Arthritis and Atherosclerosismentioning
confidence: 99%
“…However, the link between RA and atherosclerosis in genomics pathways involves shared genetic factors in inflammation, lipid metabolism, and endothelial function [69]. Epigenetic modifications may also contribute to the shared genetic basis of these diseases [61]. A better understanding of these genetic and epigenetic mechanisms could lead to new therapies for both RA and atherosclerosis.…”
Section: Shared Genes For Rheumatoid Arthritis and Atherosclerosismentioning
confidence: 99%
“…Limonova AS, et al (2021) представили клинический случай пациента с выраженной гипертриглицеридемией и ранним атеросклерозом. У пациента помимо rs7412 в гомозиготном состоянии верифицирован редкий патогенный ВНП rs267606664 (p.Gly145Asp) в гетерозиготном состоянии [11].…”
Section: патофизиология и генетическое разнообразие сдлпunclassified
“…Помимо этого, в случае выявления у пробанда аутосомно-доминантной формы заболевания возможен каскадный скрининг родственников и, в случае выявления у родственников патогенного ВНП, наиболее раннее начало профилактических мероприятий. Таким образом, ранее выявление генотипов, ответственных за развитие СДЛП, путем проведения генетического скрининга с актуализацией первичной профилактики, способно предотвратить развитие фенотипа СДЛП и, тем самым, снизить риск развития ССЗ и инвалидизацию у данной категории больных, что может быть экономически эффективной стратегией [11].…”
Section: профилактикаunclassified